2021
DOI: 10.1002/tox.23295
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of targeted regulatory Nrf2 gene on rats with acute brain injury induced by carbon monoxide poisoning

Abstract: Oxidative stress has been considered as an important cause of neurocyte damage induced by carbon monoxide (CO) poisoning; however, the precise mechanisms are not fully understood. The study aimed to elucidate the molecular mechanism and the neuroprotective effect of targeted regulatory nuclear factor erythroid2‐related factor 2 (Nrf2) gene on acute brain injury in CO poisoning rats. An acute CO poisoning rat model was established by CO inhalation in hyperbaric oxygen chamber and followed by the administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…In this study, the simultaneous reduction in mRNA levels of these two genes following CCl 4 intervention may have contributed to the onset of oxidative stress. In addition, other genes involved in biochemical reactions downstream of glutathione metabolism, Gpx7 , Ggct , Gstp3 , Gpx2 , Chac1 , Gpx6 and Gclc , were decreased in expression in the model group, suggesting a deregulation of redox homeostasis ( Yadav et al, 2019 ; He et al, 2021 ; Tian et al, 2021 ; Zhou et al, 2021 ). We found several key genes associated with glutathione metabolism, including Gclc , Gpx7 , Chac1 and Gstt1 , which were negatively correlated with L-Glutamate.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the simultaneous reduction in mRNA levels of these two genes following CCl 4 intervention may have contributed to the onset of oxidative stress. In addition, other genes involved in biochemical reactions downstream of glutathione metabolism, Gpx7 , Ggct , Gstp3 , Gpx2 , Chac1 , Gpx6 and Gclc , were decreased in expression in the model group, suggesting a deregulation of redox homeostasis ( Yadav et al, 2019 ; He et al, 2021 ; Tian et al, 2021 ; Zhou et al, 2021 ). We found several key genes associated with glutathione metabolism, including Gclc , Gpx7 , Chac1 and Gstt1 , which were negatively correlated with L-Glutamate.…”
Section: Discussionmentioning
confidence: 98%
“…After carbon monoxide poisoning, the formation of COHb and the direct toxicity of CO lead to tissue hypoxia. Tissue hypoxia-induced oxidative stress and the neuroinflammatory response persists a long time after CO exposure, which induces apoptosis and necrosis of brain cells, ultimately leading to a wide range of neuropathological and physiological alterations 24 , 25 . In this study, we observed and analyzed the data on days one, seven, and 14 after CO poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction and RT‐qPCR detection were carried out as described previously 30 . Brain tissues of the mouse ipsilateral hemisphere were taken for RT‐qPCR analysis 3 days after operation.…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction and RT-qPCR detection were carried out as described previously. 30 Brain tissues of the mouse ipsilateral hemisphere were taken for RT-qPCR analysis 3 days after operation. TRIzol reagent (Invitrogen) was used to extract total RNA from cells and tissues in accordance with the manufacturer's protocol; 1 μg of extract RNA was reverse transcribed into Single-strand cDNA by using a First-strand cDNA Synthesis Kit (Takara).…”
Section: Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%